A high-strength and wear-resistant PE plastic and its preparation process
Through the combination of modified polyimide fiber and polyethylene grafted maleic anhydride, the problem of insufficient strength and wear resistance of polyethylene PE plastics is solved, and its hardness and wear resistance are significantly improved. It is suitable for a variety of application fields .
Patent Information
- Application Number
- CN202410609198.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-16
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2044-05-16
AI Technical Summary
The poor strength and wear resistance of traditional polyethylene PE plastics limit their development in various application fields.
Using modified polyimide fibers, high-strength wear-resistant PE plastics are prepared by spinning and plasma treatment of phenylsiloxane polyamic acid solution, combined with polyethylene grafted maleic anhydride, lubricant and antioxidant. .
The hardness, bending strength and bending modulus of polyethylene PE plastics are significantly improved, the wear amount is reduced, the wear resistance is enhanced, and the compatibility between polyimide fiber and polyethylene resin is improved.
Smart Images

Figure BDA0004843066010000041 
Figure BDA0004843066010000081 
Figure BDA0004843066010000082
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polyethylene, in particular to a high-strength and wear-resistant PE plastic and a preparation process thereof. Background Art
[0002] Polyethylene PE plastics are widely used in cables, electronic products, pipes, daily plastics, packaging materials and other fields. With the widespread use of polyethylene, the development and application of traditional polyethylene are limited due to its low strength and poor wear resistance. Therefore, higher requirements are put forward for the performance of polyethylene plastics, such as strength, hardness, wear resistance and other properties.
[0003] Polymer fibers such as polyimide fibers, polyacrylonitrile fibers, and cellulose fibers have high heat resistance, wear resistance, and mechanical strength, and are widely used in the field of plastics. Silicone polymers have strong heat resistance, good wear resistance, and stable chemical properties. They are a functional new material that can be used as a toughening agent, release agent, and impact modifier, and are widely used in materials such as polyethylene and polystyrene. However, polyimide fibers and silicone polymers are not compatible with polyethylene, and will affect the mechanical properties of polyethylene after blending with polyethylene. Summary of the invention
[0004] The technical problem to be solved is: a modified polyimide fiber is prepared to solve the problem of poor strength and wear resistance of polyethylene PE plastic.
[0005] Technical solution:
[0006] A preparation process of high-strength and wear-resistant PE plastic, comprising 100 parts by weight of polyethylene resin, 3-15 parts by weight of modified polyimide fiber, 1-6 parts by weight of polyethylene grafted maleic anhydride, 1-1.8 parts by weight of lubricant stearic acid, and 0.3-0.8 parts by weight of antioxidant;
[0007] The preparation process of high-strength and wear-resistant PE plastic includes the following steps:
[0008] S1. Add phenylsiloxane polyimide fiber to a low-temperature plasma treatment apparatus, introduce oxygen and control the gas pressure to 10-15 Pa, the power to 80-150 W, and treat for 2-5 minutes to obtain modified polyimide fiber.
[0009] S2. Add polyethylene resin, modified polyimide fiber, polyethylene grafted maleic anhydride, lubricant stearic acid, and antioxidant into a screw extruder, melt extrude, and granulate to obtain high-strength and wear-resistant PE plastic.
[0010] The preparation process of phenylsiloxane polyimide fiber comprises the following steps:
[0011] S3: Add tetrahydrofuran and toluene mixed solvent, triethylamine and 4-hydroxyphthalic anhydride to a flask, stir and dissolve, add tetrahydrofuran solution of diphenyldichlorosilane dropwise at 35-50°C, wherein the ratio of triethylamine, 4-hydroxyphthalic anhydride and diphenyldichlorosilane is (2.2-2.6) mol: (1.8-2.4) mol: 1 mol, react for 24-48 hours, cool, distill under reduced pressure, wash with acetone, and obtain phenylsiloxane dianhydride intermediate. The structural formula is:
[0012] S4: Add N,N-dimethylacetamide, pyromellitic anhydride, phenylsiloxane dianhydride intermediate, and diamine compound into a flask, wherein the ratio of pyromellitic anhydride, phenylsiloxane dianhydride intermediate, and diamine compound is (0.6-0.8) mol: (0.2-0.4) mol: 1 mol, and react with stirring at room temperature in a nitrogen atmosphere for 12-24 hours to obtain a phenylsiloxane polyamic acid solution.
[0013] S5. Add the phenylsilicone polyamide acid solution into the spinning tank, let it stand for degassing, and then perform dry-jet wet spinning. Place the fiber in an oven for gradient temperature treatment. Finally, place the fiber in a hot stretching furnace for hot stretching in a nitrogen atmosphere to obtain phenylsilicone polyimide fiber.
[0014] Among them, the diamine compounds in S4 include p-phenylenediamine, diphenylenediamine, 4,4-diaminodiphenylmethane, 3,3',5,5'-tetramethyl-4,4'-diaminodiphenylmethane, and 4,4-diaminodiphenyl ether.
[0015] The coagulation bath for spinning in S5 is an aqueous solution of N,N-dimethylacetamide with a volume fraction of 30-40%. During the spinning process, the spray-draw ratio is controlled to be 2-3 and the draft ratio is controlled to be 1.5-3.
[0016] Among them, the gradient temperature rise treatment in S5 is successively at 60°C for 3-5h, 100°C for 2h, 160°C for 2h, 250°C for 2h, 250°C for 2h, and 300°C for 1h.
[0017] Among them, the temperature of hot drawing in S5 is 400-450°C, and the drawing ratio is 1.5-3 times.
[0018] Technical effect: The present invention uses 4-hydroxyphthalic anhydride and diphenyldichlorosilane as reactants to prepare a phenylsiloxane dianhydride intermediate, which is then polymerized with diamine compounds such as pyromellitic anhydride and p-phenylenediamine to obtain a phenylsiloxane polyamic acid solution, and finally subjected to dry-jet wet spinning, gradient heating thermal imidization and heat stretching treatment to obtain a polyimide fiber containing a phenylsiloxane structure.
[0019] The present invention modifies phenylsiloxane polyimide fiber by plasma treatment, introduces hydroxyl groups on the fiber surface, uses polyethylene grafted maleic anhydride as a compatibilizer, and its anhydride groups can react with hydroxyl groups on the fiber surface, thereby improving the compatibility between the polyimide fiber and the polyethylene resin, enhancing the interfacial force between the two, and allowing the polyimide fiber to be well dispersed in the polyethylene resin matrix. The polyimide fiber contains structures such as phenylsiloxane structure and rigid imide ring, which can effectively improve the Shore hardness, bending strength, and bending modulus of polyethylene PE plastic, reduce wear, and improve wear resistance. DETAILED DESCRIPTION
[0020] For ease of understanding of the present invention, preferred embodiments of the present invention are provided below. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive.
[0021] (1) Add a mixed solvent of tetrahydrofuran and toluene, 33-39 mmol of triethylamine and 27-36 mmol of 4-hydroxyphthalic anhydride into a flask, stir and dissolve, add dropwise a tetrahydrofuran solution containing 15 mmol of diphenyldichlorosilane at 35-50° C., react for 24-48 hours, cool, distill under reduced pressure, and wash with acetone to obtain a phenylsiloxane dianhydride intermediate.
[0022] (2) Add N,N-dimethylacetamide, 6-8 mmol of pyromellitic anhydride, 2-4 mmol of phenylsiloxane dianhydride intermediate, 10 mmol of p-phenylenediamine, benzyl diamine, 4,4-diaminodiphenylmethane, 3,3',5,5'-tetramethyl-4,4'-diaminodiphenylmethane, or any one of 4,4-diaminodiphenyl ether into a flask, and stir the reaction at room temperature in a nitrogen atmosphere for 12-24 hours to obtain a phenylsiloxane polyamic acid solution.
[0023] (3) Add phenylsilicone polyamide acid solution to a spinning tank, let it stand for degassing, and then perform dry-jet wet spinning, using an aqueous solution of N,N-dimethylacetamide with a volume fraction of 30-40% as a coagulation bath, controlling the spray-draw ratio to 2-3, and the draft ratio to 1.5-3; placing the fiber in an oven for gradient temperature treatment, sequentially treating at 60°C for 3-5h, 100°C for 2h, 160°C for 2h, 250°C for 2h, 250°C for 2h, and 300°C for 1h; finally, placing the fiber in a hot stretching furnace, performing hot stretching in a nitrogen atmosphere, controlling the temperature to 400-450°C, and the draft ratio to 1.5-3 times, to obtain phenylsilicone polyimide fiber.
[0024] (4) Add phenylsiloxane polyimide fiber to a low-temperature plasma treatment apparatus, introduce oxygen and control the gas pressure to 10-15 Pa, the power to 80-150 W, and treat for 2-5 minutes to obtain modified polyimide fiber.
[0025] (5) Add 500 g of polyethylene resin, 15-75 g of modified polyimide fiber, 5-30 g of polyethylene grafted maleic anhydride, 5-9 g of lubricant stearic acid, and 1.5-4 g of antioxidant 168 into a screw extruder, melt extrude, and granulate to obtain high-strength and wear-resistant PE plastic.
[0026] Example 1
[0027] Add 100 mL of tetrahydrofuran and 20 mL of toluene mixed solvent, 39 mmol of triethylamine and 36 mmol of 4-hydroxyphthalic anhydride to a flask, stir to dissolve, add 50 mL of tetrahydrofuran solution containing 15 mmol of diphenyldichlorosilane dropwise at 35°C, react for 48 hours, cool, distill under reduced pressure, wash with acetone, and obtain phenylsiloxane dianhydride intermediate. The reaction formula is as follows:
[0028]
[0029] 40 mL of N,N-dimethylacetamide, 8 mmol of pyromellitic anhydride, 2 mmol of phenylsiloxane dianhydride intermediate, and 10 mmol of p-phenylenediamine were added to a flask, and the mixture was stirred and reacted at room temperature in a nitrogen atmosphere for 12 h to obtain a phenylsiloxane polyamic acid solution.
[0030] Add phenylsilicone polyamide acid solution to the spinning tank, let it stand for degassing, and then carry out dry-jet wet spinning, use an aqueous solution of N,N-dimethylacetamide with a volume fraction of 35% as a coagulation bath, control the spray-draw ratio to 2.5, and the draft ratio to 2; place the fiber in an oven for gradient temperature treatment, and treat it at 60°C for 4h, 100°C for 2h, 160°C for 2h, 250°C for 2h, 250°C for 2h, and 300°C for 1h in sequence; finally, place the fiber in a hot stretching furnace, perform hot stretching in a nitrogen atmosphere, control the temperature to 400°C, and the draft ratio to 2 times to obtain phenylsilicone polyimide fiber.
[0031] Phenylsiloxane polyimide fiber was added into a low-temperature plasma treatment apparatus, oxygen was introduced and the gas pressure was controlled to be 10 Pa, the power was 120 W, and the treatment was performed for 3 minutes to obtain modified polyimide fiber.
[0032] Add 500g polyethylene resin, 15g modified polyimide fiber, 5g polyethylene grafted maleic anhydride, 5g lubricant stearic acid, and 4g antioxidant 168 into a screw extruder and melt extrude. The temperatures in zones 1-6 are 150°C, 180°C, 190°C, 210°C, 210°C, and 205°C. The screw speed is 150r / min. Granulation is performed to obtain high-strength and wear-resistant PE plastic.
[0033] Example 2
[0034] Add 100 mL of tetrahydrofuran and 30 mL of toluene mixed solvent, 33 mmol of triethylamine and 27 mmol of 4-hydroxyphthalic anhydride into a flask, stir to dissolve, add 50 mL of tetrahydrofuran solution containing 15 mmol of diphenyldichlorosilane dropwise at 50°C, react for 24 hours, cool, distill under reduced pressure, and wash with acetone to obtain a phenylsiloxane dianhydride intermediate.
[0035] 50 mL of N,N-dimethylacetamide, 7 mmol of pyromellitic anhydride, 3 mmol of phenylsiloxane dianhydride intermediate, and 10 mmol of 4,4-diaminodiphenyl ether were added to a flask, and the mixture was stirred and reacted at room temperature in a nitrogen atmosphere for 18 h to obtain a phenylsiloxane polyamic acid solution.
[0036] Add phenylsilicone polyamide acid solution into the spinning tank, let it stand for degassing, and then carry out dry-jet wet spinning, use 40% by volume of N, N-dimethylacetamide aqueous solution as coagulation bath, control the spray-draw ratio to 2, and the draft ratio to 1.5; place the fiber in an oven for gradient temperature treatment, and treat it at 60°C for 4h, 100°C for 2h, 160°C for 2h, 250°C for 2h, 250°C for 2h, and 300°C for 1h in sequence; finally, place the fiber in a hot stretching furnace, perform hot stretching in a nitrogen atmosphere, control the temperature to 400°C, and the draft ratio to 1.5 times to obtain phenylsilicone polyimide fiber.
[0037] Phenylsiloxane polyimide fiber was added into a low-temperature plasma treatment apparatus, oxygen was introduced and the gas pressure was controlled to be 15 Pa, the power was 80 W, and the treatment was performed for 5 minutes to obtain modified polyimide fiber.
[0038] Add 500g polyethylene resin, 40g modified polyimide fiber, 18g polyethylene grafted maleic anhydride, 9g lubricant stearic acid, and 1.5g antioxidant 168 into a screw extruder and melt extrude. The temperatures in zones 1-6 are 150°C, 180°C, 190°C, 210°C, 210°C, and 205°C. The screw speed is 150r / min. Granulation is performed to obtain high-strength and wear-resistant PE plastic.
[0039] Example 3
[0040] Add 100 mL of tetrahydrofuran and 30 mL of a mixed solvent of toluene, 36 mmol of triethylamine and 32 mmol of 4-hydroxyphthalic anhydride into a flask, stir to dissolve, add dropwise 50 mL of a tetrahydrofuran solution containing 15 mmol of diphenyldichlorosilane at 40°C, react for 36 hours, cool, distill under reduced pressure, and wash with acetone to obtain a phenylsiloxane dianhydride intermediate.
[0041] Add 50 mL of N,N-dimethylacetamide, 6 mmol of pyromellitic anhydride, 4 mmol of phenylsiloxane dianhydride intermediate, and 10 mmol of 4,4-diaminodiphenylmethane into a flask, and stir the reaction at room temperature in a nitrogen atmosphere for 24 hours to obtain a phenylsiloxane polyamic acid solution.
[0042] Add phenylsilicone polyamide acid solution into the spinning tank, let it stand for degassing, and then carry out dry-jet wet spinning, use 30% by volume of N, N-dimethylacetamide aqueous solution as coagulation bath, control the spray-draw ratio to be 3, and the draft ratio to be 3; place the fiber in an oven for gradient temperature treatment, and treat it at 60°C for 3h, 100°C for 2h, 160°C for 2h, 250°C for 2h, 250°C for 2h, and 300°C for 1h in sequence; finally, place the fiber in a hot stretching furnace, perform hot stretching in a nitrogen atmosphere, control the temperature to be 450°C, and the draft ratio to be 1.5 times, to obtain phenylsilicone polyimide fiber.
[0043] Phenylsiloxane polyimide fiber was added into a low-temperature plasma treatment apparatus, oxygen was introduced and the gas pressure was controlled to be 15 Pa, the power was 80 W, and the treatment was performed for 2 minutes to obtain modified polyimide fiber.
[0044] Add 500g polyethylene resin, 75g modified polyimide fiber, 30g polyethylene grafted maleic anhydride, 7g lubricant stearic acid, and 2.5g antioxidant 168 into a screw extruder and melt extrude. The temperatures in zones 1-6 are 150°C, 180°C, 190°C, 210°C, 210°C, and 205°C. The screw speed is 150r / min. Granulation is performed to obtain high-strength and wear-resistant PE plastic.
[0045] Comparative Example 1
[0046] Add 500g polyethylene resin, 30g polyethylene grafted maleic anhydride, 7g lubricant stearic acid, and 2.5g antioxidant 168 into a screw extruder and melt extrude. The temperatures in zones 1-6 are 150°C, 180°C, 190°C, 210°C, 210°C, and 205°C. The screw speed is 150r / min. Granulate to obtain PE plastic.
[0047] Comparative Example 2
[0048] 40 mL of N,N-dimethylacetamide, 10 mmol of pyromellitic anhydride, and 10 mmol of p-phenylenediamine were added to a flask, and the mixture was stirred and reacted at room temperature for 12 h in a nitrogen atmosphere to obtain a polyamic acid solution.
[0049] Add polyamic acid solution into the spinning tank, let it stand for degassing, and then carry out dry-jet wet spinning, use an aqueous solution of N,N-dimethylacetamide with a volume fraction of 35% as a coagulation bath, control the spray-draw ratio to 2.5, and the draft ratio to 2; place the fiber in an oven for gradient temperature treatment, and treat it at 60°C for 4h, 100°C for 2h, 160°C for 2h, 250°C for 2h, 250°C for 2h, and 300°C for 1h in sequence; finally, place the fiber in a hot stretching furnace, perform hot stretching in a nitrogen atmosphere, control the temperature to 400°C, and the draft ratio to 2 times to obtain polyimide fiber.
[0050] Add polyimide fiber into the low-temperature plasma treatment instrument, introduce oxygen and control the gas pressure to 15 Pa, the power to 80 W, and treat for 5 minutes to obtain modified polyimide fiber.
[0051] Add 500g polyethylene resin, 15g modified polyimide fiber, 5g polyethylene grafted maleic anhydride, 5g lubricant stearic acid, and 4g antioxidant 168 into a screw extruder and melt extrude. The temperatures in zones 1-6 are 150°C, 180°C, 190°C, 210°C, 210°C, and 205°C. The screw speed is 150r / min. Granulate to obtain PE plastic.
[0052] Comparative Example 3
[0053] According to the method of Example 1, phenylsiloxane polyimide fibers were prepared.
[0054] Add 500g polyethylene resin, 15g phenylsiloxane polyimide fiber, 5g polyethylene grafted maleic anhydride, 5g lubricant stearic acid, and 4g antioxidant 168 into a screw extruder and melt extrude. The temperatures in zones 1-6 are 150°C, 180°C, 190°C, 210°C, 210°C, and 205°C. The screw speed is 150r / min. Granulate to obtain PE plastic.
[0055] Comparative Example 4
[0056] According to the method of Example 1, modified polyimide fiber was prepared.
[0057] Add 500g polyethylene resin, 15g modified polyimide fiber, 5g lubricant stearic acid, and 4g antioxidant 168 into a screw extruder and melt extrude. The temperatures in zones 1-6 are 150°C, 180°C, 190°C, 210°C, 210°C, and 205°C. The screw speed is 150r / min. Granulate to obtain PE plastic.
[0058] PE plastic was injection molded into standard specimens, the temperature was controlled at 200°C and the pressure was 40MPa to obtain PE plastic specimens. The bending properties were tested according to the method of ASTM D790-2003. The Shore hardness was tested according to the method of GB T 2411-2008.
[0059]
[0060] Friction test: The test was conducted using a high-speed ring-block wear tester. Test conditions: dry friction, 45 steel ring as the friction pair, load 300N, speed 200r / min, test temperature 25℃, and the wear amount under different wear times was tested.
[0061]
[0062]
[0063] In Examples 1, 2, and 3, the phenylsiloxane polyimide fiber is modified by plasma treatment, and hydroxyl groups are introduced on the fiber surface. Polyethylene grafted maleic anhydride is used as a compatibilizer, and its anhydride groups can react with the hydroxyl groups on the fiber surface, thereby improving the compatibility between the polyimide fiber and the polyethylene resin, enhancing the interfacial force between the two, and allowing the polyimide fiber to be well dispersed in the polyethylene resin matrix. The polyimide fiber contains phenylsiloxane structure, rigid imide ring and other structures, which can effectively improve the Shore hardness, bending strength, and bending modulus of polyethylene PE plastic, reduce wear, and improve wear resistance.
[0064] In Comparative Example 1, no modified polyimide fiber was added, and the strength and wear resistance of the polyethylene PE plastic were the worst.
[0065] In Comparative Example 2, pyromellitic anhydride and p-phenylenediamine are used as polymerization monomers, and no phenylsiloxane dianhydride intermediate is added. The polyimide and plasma-modified polyimide fibers obtained do not contain phenylsiloxane structures, and the strength and wear resistance of the polyethylene plastic are poor.
[0066] The phenylsiloxane polyimide fiber of Comparative Example 3 has not been modified by plasma treatment, and has no hydroxyl groups on the surface, so it cannot react with the polyethylene grafted maleic anhydride compatibilizer, resulting in poor compatibility of the polyimide fiber in the polyethylene matrix, and poor strength and wear resistance of the polyethylene plastic.
[0067] In Comparative Example 4, plasma-modified polyimide fibers were added, but no polyethylene grafted maleic anhydride compatibilizer was added. The compatibility of the polyimide fibers in the polyethylene matrix was also poor, and the strength and wear resistance of the polyethylene plastic were poor.
[0068] The above embodiments only express the preferred implementation modes of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for those of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A process for preparing high-strength and wear-resistant PE plastic, characterized in that: The high-strength and wear-resistant PE plastic comprises 100 parts by weight of polyethylene resin, 3-15 parts by weight of modified polyimide fiber, 1-6 parts by weight of polyethylene grafted maleic anhydride, 1-1.8 parts by weight of lubricant stearic acid, and 0.3-0.8 parts by weight of antioxidant; The preparation process of the high-strength and wear-resistant PE plastic comprises the following steps: S1, adding phenylsiloxane polyimide fiber to a low-temperature plasma treatment apparatus, introducing oxygen and controlling the gas pressure to 10-15 Pa, the power to 80-150 W, and treating for 2-5 min to obtain modified polyimide fiber; S2, adding polyethylene resin, modified polyimide fiber, polyethylene grafted maleic anhydride, lubricant stearic acid, and antioxidant into a screw extruder, melt extruding, and granulating to obtain high-strength and wear-resistant PE plastic; The preparation process of the phenylsiloxane polyimide fiber comprises the following steps: S3: Add tetrahydrofuran and toluene mixed solvent, triethylamine and 4-hydroxyphthalic anhydride into a flask, stir to dissolve, add tetrahydrofuran solution of diphenyldichlorosilane dropwise at 35-50° C., react for 24-48 hours, and obtain phenylsiloxane dianhydride intermediate; S4: Add N,N-dimethylacetamide, pyromellitic anhydride, phenylsiloxane dianhydride intermediate, and diamine compound into a flask, and stir and react at room temperature for 12-24 hours in a nitrogen atmosphere to obtain a phenylsiloxane polyamic acid solution; S5, adding phenylsiloxane polyamic acid solution to a spinning tank, standing to degas, and then performing dry-jet wet spinning, placing the fiber in an oven for gradient temperature treatment, and finally placing the fiber in a hot stretching furnace for hot stretching in a nitrogen atmosphere to obtain phenylsiloxane polyimide fiber; The ratio of triethylamine, 4-hydroxyphthalic anhydride and diphenyldichlorosilane in S3 is (2.2-2.6) mol: (1.8-2.4) mol: 1 mol; The ratio of pyromellitic anhydride, phenylsiloxane dianhydride intermediate, and diamine compound in S4 is (0.6-0.8) mol: (0.2-0.4) mol: 1 mol; The diamine compounds in S4 include p-phenylenediamine, diphenylenediamine, 4,4-diaminodiphenylmethane, 3,3',5,5'-tetramethyl-4,4'-diaminodiphenylmethane, and 4,4-diaminodiphenyl ether.
2. The preparation process of high-strength and wear-resistant PE plastic according to claim 1, characterized in that: The coagulation bath for spinning in S5 is an aqueous solution of N,N-dimethylacetamide with a volume fraction of 30-40%. During the spinning process, the spray-draw ratio is controlled to be 2-3 and the draft ratio is controlled to be 1.5-3.
3. The preparation process of high-strength and wear-resistant PE plastic according to claim 1, characterized in that: The temperature of the hot stretching in S5 is 400-450° C., and the stretching ratio is 1.5-3 times.
Citation Information
Patent Citations
Nanomaterial-reinforced resins and related materials
CN103108905A
Flexible hyperbranched semi-interpenetrating fluorinated polysiloxane polyimide film and preparation method thereof
CN103113587A
Efficient energy-storage composite phase transition material and preparation method thereof
CN103666379A
Polyimide adhesive and preparation method thereof
CN104293277A
Antibacterial toughened polyethylene plastic pipe and preparation method thereof
CN111499951A
